Ekspresi Seni Budaya Islam di Tengah Kemajemukan Masyarakat Banten - Huriyudin, Huriyudin (Jurnal Lektur Keagamaan, 2014)
The article is based on a field study investigated the general map of religious art and culture in Banten, a province on the western tip of the island of Java , known as a strong Islamic identity. Using the theory of concentric circles and approaches the sub- division of Tawheed Art built by Razi Ismail Al-Faruqi, a work of this initial study resulted in interesting findings. Namely, the Banten community, an expression of art and culture has a high degree of heterogeneity, and fills the entire concentric circles. In fact, most of the growing culture of artistic expression in Islamic Banten not show a strong color, especially in the hilly areas and the agricultural community as well as around the coast. Islamic art and culture in Banten are generally found in urban areas and in some areas since the beginning at the center of the spread of Islam.Keywords: expression of art and culture, the concentric circles, the sub-division